Effect of MQL on Surface Roughness in Milling of AA7075-T6 - Tosun, Nihat; Huseyinoglu, Mesut (Taylor & Francis Inc, 2010)
In this study, the effect of cutting parameters and cooling technique on the workpiece surface roughness in milling of 7075-T6 aluminum alloy was experimentally investigated. Experiments were conducted under different spindle speed, feed rate, cooling technique (conventional and minimum quantity lubrication), and cutting tool material. The effect of volumetric concentration of solution for minimum quantity lubrication (MQL) was also investigated. The cutting fluid is a mixture of boron oil and water. The cutting fluid in milling with MQL was delivered to the interface workpiece and cutting tool as atomize. The experimental results for surface roughness were statistically analyzed by using analysis of variance (ANOVA).
Keywords: Aluminum; ANOVA; Milling; MQL; Surface roughness